Pelabelan Harmonis Ganjil pada Kelas Graf Baru Hasil Operasi Cartesian Product - Fery Firmansah; Muhammad Ridlo Yuwono (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2017)
Graph class which has the characteristic of odd harmonious labeling is called as odd harmonious graph. Net graph is a graph which is gained by using operation Cartesian product of two line graphs. The construction of snake-net graph is inspired by the definition of snake graph replacing the round graph to net graph. In this paper, the study will show that snake-net graph fulfill the characteristic of odd harmonious graph in such a way snake-net graph is the odd harmonious graph. In the end of this paper, it is also shown that the union of snake-net graph is also called as the odd harmonious graph.